Raising Children in Times of Change: Parenting and Resilience in an Indus-trializing Coastal Community - Maslakhatul Ainiyah; Auditya Purwandini Sutarto; Nailul Izzah; Mohammad Ririn Rosyidi; Rista Bintarawita Megasari (Indigenous: Jurnal Ilmiah Psikologi, 2025)
Coastal communities in Indonesia are undergoing rapid transformation due to industrial expansion, yet little is known about how families adapt to such disruptions. This study examines family resilience in Mengare, Gresik, East Java, in the context of environmental decline and exclusion from industrial employment following the Java Integrated Industrial and Ports Estate (JIIPE) development. Using a qualitative approach, data were collected through in-depth interviews with 14 parents and community members and one focus group discussion with six teachers, village officials, and religious leaders. Thematic analysis, guided by Walsh’s family resilience framework and Bronfenbrenner’s ecological systems theory, identified six themes: economic strain and adaptive livelihoods; parenting and family processes; education and skills gap; spirituality as a coping and meaning-making resource; social cohesion and community bonds; and future concerns and uncertainty. Families displayed resilience by reorganizing roles, relying on communal spirituality, and maintaining social cohesion. However, dual pressures constrained these processes: ecological degradation reducing fishing and pond yields, and industrial exclusion limiting access to new employment. Parenting norms emphasized harmony and emotional closeness but provided limited developmental support, while spirituality sustained vertical resilience without equipping families for horizontal adaptation to labor market demands. The findings indicate that resilience in Mengare is present but bounded, anchored in endurance rather than transformation. Policy interventions should prioritize bridging school–industry gaps, strengthening soft skills, and fostering collaboration among households, schools, and local institutions to support adaptive resilience in the face of industrial change